(untitled) (E Global Congress, 2023)
The legal culture of a society plays a crucial role in maintaining justice, equality, and social harmony. While significant efforts have been made to improve legal awareness and education in urban areas, rural populations often lag behind. Enhancing the legal culture of the rural population is a complex task that requires a comprehensive understanding of the socio-philosophical aspects involved. This article aims to explore the various dimensions of raising the legal culture of rural communities, including the challenges faced, potential strategies, and the importance of integrating cultural and social factors into the process. By addressing these aspects, policymakers, educators, and stakeholders can gain valuable insights to develop effective initiatives that empower the rural population with legal knowledge and promote a more just and equitable society.